2018
DOI: 10.1016/j.scitotenv.2017.11.324
|View full text |Cite
|
Sign up to set email alerts
|

What is socio-ecological research delivering? A literature survey across 25 international LTSER platforms

Abstract: With an overarching goal of addressing global and regional sustainability challenges, Long Term Socio-Ecological Research Platforms (LTSER) aim to conduct place-based research, to collect and synthesize both environmental and socio-economic data, and to involve a broader stakeholder pool to set the research agenda. To date there have been few studies examining the output from LTSER platforms. In this study we enquire if the socio-ecological research from 25 self-selected LTSER platforms of the International Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 41 publications
(64 reference statements)
0
43
0
Order By: Relevance
“…[34] plus the three incorporated in 2010. Nowadays, the number has increased to 31 [35] and more have been created in other LTER regional networks [36]. (b) Location of Kiskun LTSER platform in Hungary (green area) and the ExDRain experiment site (red dot).…”
Section: Exdrain Experimentsmentioning
confidence: 99%
“…[34] plus the three incorporated in 2010. Nowadays, the number has increased to 31 [35] and more have been created in other LTER regional networks [36]. (b) Location of Kiskun LTSER platform in Hungary (green area) and the ExDRain experiment site (red dot).…”
Section: Exdrain Experimentsmentioning
confidence: 99%
“…Comparisons with the normative model for LTSER platforms LTSER emerged in response to the recognition of increased effects of human activities on sustainability at local to global levels (Singh et al 2013;Mirtl et al 2018). These challenges can often be considered as wicked (Duckett et al 2016), which calls for integrative modes of knowledge production and learning (Angelstam et al 2013b;Holzer et al 2018). With the aim of monitoring and diagnosing, as well as treating socio-ecological systems by contributing to problemsolving, the LTSER platform concept aims at being a type of place-based infrastructure that supports collaborative knowledge production and learning by academic and non-academic participants (Haberl et al 2006;Singh et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Conditions for joining the LTSER network (usually) include: support by the platform's local, regional and national authorities, the existence of long-term datasets (especially biodiversity indicators but also abiotic variables) and the inclusion and integration of socio-economic data (Haberl et al 2006(Haberl et al , 2009Mirtl et al 2013). Dick et al (2018) showed that this vision has become reality in terms of a rapid increase of research publications. Enhancing collaboration among LTSER platforms at the international level is the next desirable level of ambition towards using multiple landscapes as a laboratory (Angelstam et al 2013a;Holzer et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental changes affect ecological systems and their ability to provide ecosystem services, so the changes in ecosystem services affect provisions on the welfare of the social system (Fisher et al, 2014). A clear focus on environmental sustainability is necessary in order to mitigate the longterm consequences of ecosystems, with attention to interactions with socio-economic and environmental drivers at different temporal and spatial scales (Dick et al, 2018).…”
Section: Introductionmentioning
confidence: 99%